2016
DOI: 10.15171/hpp.2016.16
|View full text |Cite
|
Sign up to set email alerts
|

Media coverage of the Ebola virus disease in four widelycirculated Nigerian newspapers: lessons from Nigeria

Abstract: Background: The importance of the media in the coverage of Ebola virus disease (EVD) in Nigeria and its implications (negative or positive) amongst the populace cannot be overemphasized.This study was conducted to assess the role of media in the Ebola reportage and its implication in creating awareness and stopping the spread amongst the populace. Methods: The nature and extent of media coverage about Ebola in four major national newspapers were examined. The four major national newspapers were The Sun, The V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 6 publications
2
11
0
Order By: Relevance
“…However, sensationalized media reporting on Ebola in areas outside the outbreak may have indirectly encouraged discrimination against Nigerians. In line with a previous quantitative analysis of Nigerian news articles, 8 "discrimination due to Ebola" was a major topic of news articles published by the Vanguard. Infectious disease outbreaks are not only public health challenges.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…However, sensationalized media reporting on Ebola in areas outside the outbreak may have indirectly encouraged discrimination against Nigerians. In line with a previous quantitative analysis of Nigerian news articles, 8 "discrimination due to Ebola" was a major topic of news articles published by the Vanguard. Infectious disease outbreaks are not only public health challenges.…”
Section: Discussionsupporting
confidence: 68%
“…4,5 Studies have explored coverage of the 2014 Ebola outbreak in media outlets such as Twitter, 6 Google, 4 YouTube 7 and print news media. 5,8 In a quantitative analysis of 301 articles published in three leading US newspapers, the most common topic was cases in the United States (39.0%), followed by the outbreak in West Africa (33.6%). 5 In contrast, in a quantitative analysis of 1625 articles published in four leading newspapers in Nigeria, the most common topic was Ebola cases in Nigeria (17.5%), followed by discrimination due to Ebola (10.8%).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…21 Therefore, working with the journalists and the media to help them understand the science and epidemiology, particularly in a fast and moving event, will improve risk communication to the public and reduce inappropriate concerns and panic. 21 However, previous studies on media reportage of heath crises reveal that even though there exists sufficient scholarly discourse on media reportage of previous disease outbreaks such as Zika virus, influenza, flu, Ebola, and Lassa fever, [16][17][18][19][22][23][24] no empirical study on media framing of the current coronavirus outbreak was found. The need to fill this lacuna in the existing literature of media reportage of health crises necessitated this present study, and it is coming at a time when the COVID-19 outbreak is on the rapid increase all over the world.…”
Section: Mass Media and Coronavirusmentioning
confidence: 99%
“…Only few studies investigate media reporting on Ebola in the affected countries themselves. Two studies looked at how the Ebola crisis was framed by newspapers from the US and Canada, compared to an “insider” perspective of an Ebola affected country (Sierra Leone and Nigeria) [ 36 , 37 ]; one assessed the role of four Nigerian newspapers in creating awareness to stop the spread of Ebola [ 38 ]. To our knowledge, however, there is no study on media reporting in the Ebola epidemic in Liberia and no research so far has been published on the portrayal of Ebola survivors in the media during the epidemic in West Africa.…”
Section: Introductionmentioning
confidence: 99%